3T MR-based treatment planning for radiotherapy of brain lesions - Stanescu, Teodor (Radiology and oncology (Ljubljana), 2006)
Purpose. The aim of this work is to develop a complete treatment planning procedure for radiation therapy of intracranial lesions based solely on 3T magnetic resonance imaging (MRI), i.e. MRI simulation. Methods. The proposed 3T MR-based radiotherapy treatment planning procedure consists of converting the MR images into CT-like images by assigning electron density information (related to CT values) to organ structures. Firstly, the 3D distortion field present in the MR volumes is determined and rectified by using an in-house developed distortion correction method. The MR volumes are segmented into anatomical structures, i.e. brain, bone and scalp, by using a combination of the "Profile" and Autocontouring" tools available on Pinnacle (Philips MedicalSystems) treatment planning system (TPS). Bulk electron density values are assigned to the 3D volumes in Pinnacle by overriding thei default MR values. Once the MR images contain the target volume along with the electron density information, they are ready to be used for dose calculations. The resulting CT+MR and MR only based plans were compared in terms of isodose distributions and dose-volume histrograms (DVHs). For plan ranking we use a tumor-control probability (TCP)-based procedure for heterogeneous irradiation,which does not require the knowledge of radiobiological parameters. Results. For all patients investigated, the 3T MR only and CT+MR-based plans are in good agreement in terms of isodose distributions, DVHs and TCPs (within 1%) following our clinical criteria. Conclusions. The proposed 3T MR only based treatment planning procedure performs as good as thestandard clinical procedure that relies on both CT and MR studies. MRI simulation can significantly reduce the patient treatment cost and save staff and machine time, and avoid any errors that may be associated with the image fusion process.
Keywords: Brain Neoplasms; možgani; novotvorbe; radiološko zdravljenje; Radiotherapy; rak (medicina); tumor